Factors influencing obstetric referral decisions and practices: A qualitative study among skilled health personnel in Kampala, Uganda - Birabwa, Catherine; Waiswa, Peter; Beňová, Lenka; Kikula, Amani; Molenaar, Jil; Banke-Thomas, Aduragbemi; van Olmen, Josefien (Elsevier Ltd, 2026)
Effective referral is crucial for maternal and perinatal survival. Understanding the referral decision-making processes and practices of skilled health personnel (SHP) is essential for addressing inefficiencies and improving health outcomes. We explored inter-facility referral linkages and factors influencing obstetric referral decisions and practices, using a behavioural approach and drawing on SHP’s perceptions. We conducted semi-structured interviews with 45 SHP working in Kampala, Uganda, between October 2023 and April 2024. We employed a thematic and framework analysis approach, using the capability, opportunity, motivation, and behaviour model to examine factors influencing referral decisions and practices. Referrals of women with obstetric complications from all levels of care were commonly directed to the National Referral Hospital. These referral linkages were influenced by factors such as proximity, the hospital’s acceptance of patients, and perceptions of lack of readiness at designated receiving facilities. Resource shortages, including the absence of critical staff and inadequate infrastructure, such as limited operating theatre space and unavailability of ambulances, commonly contributed to referrals and hindered SHP from implementing recommended referral practices, such as professional accompaniment. Additionally, SHP faced several demotivating process challenges during referrals, including lengthy patient handover processes at receiving facilities and negative or disrespectful interactions with colleagues. Our findings show that SHP in Kampala are unable to implement recommended referral practices as expected primarily due to insufficient physical opportunities, which also affect their motivation. Inadequate resources and negative or disrespectful provider conduct remain key challenges. Policymakers and implementers should improve resource availability, streamline referral processes, and enhance collaboration among SHP to facilitate appropriate referrals. [Display omitted] •Obstetric referrals are primarily directed to one referral hospital.•Structural, normative, and functionality factors influence the referral destination.•Opportunities for providers to refer appropriately are limited.•Process-related challenges demotivate providers from referring appropriately.•Resource shortages are key drivers of poor provider referral practices. Subjects